Role of sirtuins in epigenetic regulation and aging control - E. M. Samoilova; S. E. Romanov; D. A. Chudakova; P. P. Laktionov (Вавиловский журнал генетики и селекции)
Advances in modern healthcare in developed countries make it possible to extend the human lifespan, which is why maintaining active longevity is becoming increasingly important. After the sirtuin (SIRT) protein family was discovered, it started to be considered as a significant regulator of the physiological processes associated with aging. SIRT has deacetylase, deacylase, and ADPribosyltransferase activity and modifies a variety of protein substrates, including chromatin components and regulatory proteins. This multifactorial regulatory system affects many processes: cellular metabolism, mitochondrial functions, epigenetic regulation, DNA repair and more. As is expected, the activity of sirtuin proteins affects the manifestation of classic signs of aging in the body, such as cellular senescence, metabolic disorders, mitochondrial dysfunction, genomic instability, and the disruption of epigenetic regulation. Changes in the SIRT activity in human cells can also be considered a marker of aging and are involved in the genesis of various agedependent disorders. Additionally, experimental data obtained in animal models, as well as data from population genomic studies, suggest a SIRT effect on life expectancy. At the same time, the diversity of sirtuin functions and biochemical substrates makes it extremely complicated to identify causeandeffect relationships and the direct role of SIRT in controlling the functional state of the body. However, the SIRT influence on the epigenetic regulation of gene expression during the aging process and the development of disorders is one of the most important aspects of maintaining the homeostasis of organs and tissues. The presented review centers on the diversity of SIRT in humans and model animals. In addition to a brief description of the main SIRT enzymatic and biological activity, the review discusses its role in the epigenetic regulation of chromatin structure, including the context of the development of genome instability associated with aging. Studies on the functional connection between SIRT and longevity, as well as its effect on pathological processes associated with aging, such as chronic inflammation, fibrosis, and neuroinflammation, have been critically analyzed.